مكانة النازح البيئي في إطار القانون الدولي - بونصيار, ويزة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدراسة إلى البحث في المركز القانوني للنازح البيئي ضمن القانون الدولي، لانتشار هذه الظاهرة في الآونة الأخيرة من جهة، وتنوع المشكلات البيئية من جهة أخرى، من خلال الانطلاق من إشكالية فحواها: مدى إمكانية استفادة النازح البيئي من الحماية الدولية المقررة بالنصوص النافذة؟. وقد خلص هذا البحث إلى مجموعة من النتائج، ومن ذلك، أنه لا يوجد تعريف شامل ودقيق للنازح البيئي، وأنه بالرغم من انتشار هذه الظاهرة في الآونة الأخيرة، إلا أنه لا توجد اتفاقية دولية خاصة بهم، لاسيما إذا علمنا بأن اتفاقية جنيف حول اللاجئين لسنة 1951 لم تتضمن تدابير قانونية خاصة بالنازح البيئي، وأيضا هناك قصور يعتري النصوص القانونية الدولية النافذة اتجاه النازح البيئي. Abstract: This study aims to search the legal status of the environmental displaced within the international law, and the diversity of environmental problems on the other hand and by starting from the problematic of its content: To what extent can the environmental displaced benefit from the international protection stipulated in the texts in force?.his research has reached a set of results, and of that, there is no comprehensive and accurate definition of an environmental displacement despite the spread of this phenomenon recently, there is no international agreement for them. Especially if we know that the Geneva Convention on Refugees of 1951 did not include legal measures related to environmental displacement, and there are also deficiencies in the international legal texts in force towards the environmental displaced.